Інтегрована гібридна технологія паралельних обчислень - Шквар, Є. О. (НТУ "ХПІ", 2010)
The efficiency of integrated hybrid parallel technology of resource-intensive computations is analyzed. It is oriented on the use of cluster computer systems with multiprocessor or multicore nodes, which are able to realize simultaneous symmetric and distributed types of multiprocessing. The examples of the proposed approach are presented; the reasons of computational productivity scaling delay as a result of growing the processing power of distributed system are analyzed. The priority guidelines of the developed computational method are worked out.
Keywords: обчислювальні системи; паралельні обчислення; моделювання процесів; обробка інформації; гідроаеродинаміка; моделювання обтікання; паралельні алгоритми; багатоядерний процесор; паралельна архітектура